In vitro screening of antagonistic activity of microorganisms against anthracnose disease - Pešaković Marijana; Tomić Jelena; Rilak Boris; Karaklajić-Stajić Žaklina; Mandić Leka; Đurović Vesna; Vasić Tanja (Acta Agriculturae Serbica, 2022)
Anthracnose disease can be successfully controlled by chemical pesticides in conventional fruit growing. However, in organic farming, in order to maintain environmental safety and fulfill consumer demand for pesticide-free food, the control of this disease is a major problem. The use of biocontrol agents with the antagonistic mechanism of control of many phytopathogens is an innovative alternative for cost-effective and eco-friendly production. The antagonistic activities of Trichoderma viride and Bacillus subtilis were tested in vitro against Colletotrichum acutatum, one of major plant pathogens responsible for anthracnose. The microbial antagonists inhibited mycelial growth in the dual culture. T. viride exhibited strong antagonism against C. acutatum isolates (80%). The B. subtilis isolate also had a strong effect on inhibiting the development of C. acutatum (37.5%). The results of this study identified T. viride and B. subtilis as promising biological control agents for further testing against anthracnose disease in fruits.